Perpesi Tentang Penggunaan Antigout Konvensional-Fitoterapi Terhadap Efektivitas Terapi Pasien Gout Arthritis di Puskesmas Kedungwuni I - Sisca Windy Prastika; Wulan Agustin Ningrum; Ainun Muthoharoh; St. Rahmatullah (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Based on data from the Pekalongan District Health Office in 2022 the highest gout arthritis occurs in the Kedungwuni area. Gout arthritis patients at Kedungwuni I Public Health Center use conventional antigout-phytotherapy to treat gout arthritis. One of the factors that influence a person in solving health problems is perception. Good perception results in good therapeutic effectiveness. The purpose of this study was to determine the relationship between perceptions about the use of conventional antigout-phytotherapy on the effectiveness of therapy for gout arthritis patients at the Kedungwuni I Public Health Center. This type of research was non-experimental with an observational method. This study uses a prospective design. Sampling of 36 respondents using total sampling with purposive sampling technique. Data was collected using a validated questionnaire, consisting of statements of perceptions about the use of conventional antigout-phytotherapy. The data obtained was carried out by univariate analysis and bivariate analysis. The results of the univariate analysis showed that the majority of respondents were female (80.6%); aged 45-59 years (55.6%); work as a housewife (44.4%); graduated from elementary school (58.3%); suffer from gout arthritis for a long time (52.8%); type of conventional drug used Allopurinol (100%); The most widely used phytotherapy was soursop leaf decoction (33.3%). Most of the respondents have a good perception (52.8%); and the effectiveness of therapy is good as seen from controlled uric acid levels (66.7%). The results of bivariate analysis using the Chi Square test obtained a significance value of 0.002 (p <0.05), which means that there is a relationship between perceptions about the use of conventional antigout-phytotherapy to the effectiveness of therapy